The living Qur’an: Kompolan tradition among children in Madura - Nurdin, Arbain; Zainab, Nurul; Sulaiman, Sulaiman Hasan (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Islam Negeri Profesor Kiai Haji Saifuddin Zuhri Purwokerto Purwokerto, 2023)
This study analyzes and examines community (children) interaction with the Qur'an in the kompolan tradition in Patereman, Modung, Bangkalan, Madura. It aims to find out about the practice of the kompolan tradition among children and the values and motivations that drive them to practice the tradition. The study employed qualitative methods as well as participant observation, in-depth interviews, and documentation for data collection. The results show that the tradition has been practiced since 2004, involving some religious activities such as reciting surah Yasin and short surah of juz 30 in a concregation. This tradition carries the value of faith and devotion to God and His Prophet as well as social values. It was also figured out that children’ participation in the tradition is driven by their inquisitiveness regarding the religious activities involved in the tradition.